Pediatricians' storytelling about positive, negative, and turning professional experiences - Chiara Fioretti; Enrica Ciucci; Daniela Carpenzano; Laura Vagnoli; Andrea Smorti (Hygeia Press di Corridori Marinella, 2021)
Background: The present study aims to explore narratives about positive, negative, and turning autobiographical memories of pediatricians, evaluating differences among the three types of narratives in terms of their structure and exploring emerged contents of narratives. Methods: Nineteen pediatricians employed in a pediatric hospital of central Italy took part in the study by narrating the low point, the high point, and the turning point of their professional experience. Researchers identified the narrative structure of collected stories. A content analysis was performed to identify the emerged themes of low points, high points, and turning points. Results: Results show that pediatricians perform better-structured narratives when they focus on low and high episodes than turning ones (Friedman test = 15.176; p = 0.001). Furthermore, low points deal with the relationship with patients and the management of emotions due to their suffering and death, high points are related to both relational and individual issues as feeling gratitude from patients, professional upgrades and success, while turning points are more related to personal and individual issues like economic growth and the achievement of resident position. Discussion: Authors discuss the importance of storytelling and autobiographical memory disclosure as a tool to help physicians to deal with the emotional impact of their professional experiences with patients.